2017
DOI: 10.1098/rsos.170507
|View full text |Cite
|
Sign up to set email alerts
|

Transition from fractional to classical Stokes–Einstein behaviour in simple fluids

Abstract: An optical technique for tracking single particles has been used to evaluate the particle diameter at which diffusion transitions from molecular behaviour described by the fractional Stokes–Einstein relationship to particle behaviour described by the classical Stokes–Einstein relationship. The results confirm a prior prediction from molecular dynamic simulations that there is a particle size at which transition occurs and show it is inversely dependent on concentration and viscosity but independent of particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…Coglitore et al found by tracking single monodispersed gold and polystyrene nanoparticles that, below a critical size and concentration, the diffusion coefficient of the nanoparticles was at least one order of magnitude smaller than the theoretical value predicted by Stokes-Einstein equation and was independent of nanoparticle size and density. The transition from the Stokes-Einstein diffusion regime to the slower diffusion regime has been reported to appear for concentration of particles in the range of 10 8 -10 9 particles m −1 [19,20].…”
Section: Resultsmentioning
confidence: 97%
“…Coglitore et al found by tracking single monodispersed gold and polystyrene nanoparticles that, below a critical size and concentration, the diffusion coefficient of the nanoparticles was at least one order of magnitude smaller than the theoretical value predicted by Stokes-Einstein equation and was independent of nanoparticle size and density. The transition from the Stokes-Einstein diffusion regime to the slower diffusion regime has been reported to appear for concentration of particles in the range of 10 8 -10 9 particles m −1 [19,20].…”
Section: Resultsmentioning
confidence: 97%
“…The dynamic viscosity of DMEM with 10%FBS has been reported to be just 5% higher than the dynamic viscosity of pure water [34], which is not enough to have a significant impact on nanoparticle kinetics [23].…”
Section: Nanoparticle Sedimentationdiffusion Equilibrium In Biologicamentioning
confidence: 97%
“…In this study we investigated the settling dynamics of different sized gold nanoparticles in water and cell culture medium at a range of different temperature exploiting the optical phenomenon of caustics [25] making the diffusion coefficient a function of the local concentration of nanoparticles, which is a factor that has been reported to influence the dynamics of nanoparticles in solution [23].…”
Section: Sedimentationdiffusion Equilibriummentioning
confidence: 99%
See 2 more Smart Citations